A first‐in‐human study of CAL101, a monoclonal antibody targeting S100A4 - Jonas Hallén; Sylvia Vetrhus; Margrethe Sørgaard; Jörg Klingelhöfer; Signe Borchert; Ian Holyer; Shruthi Ramesh; Jörg H. W. Distler; Dave Singh (British Journal of Clinical Pharmacology, 2026)
Aims S100A4 is a damage‐associated molecular pattern protein that amplifies pro‐inflammatory and pro‐fibrotic signalling. CAL101 is a first‐in‐class humanized monoclonal antibody that neutralizes S100A4. This first‐in‐human study evaluated safety, pharmacokinetics (PK), immunogenicity and exploratory pharmacodynamics (PD) of CAL101. Methods This Phase 1, randomized, double‐blind, placebo‐controlled study, included two parts. Part A assessed single ascending intravenous doses of CAL101 (0.5–20 mg/kg) or placebo in 40 healthy volunteers. Part B evaluated multiple ascending doses, 4 infusions of CAL101 (10 and 20 mg/kg) or placebo every 3 weeks, in 17 patients with mild‐to‐moderate psoriasis. The primary endpoint was safety and tolerability. Results CAL101 was well tolerated, with no dose‐limiting toxicities or serious adverse events. Treatment‐emergent adverse events were balanced between treatment groups. The PK profile showed target‐mediated, nonlinear kinetics at lower doses. Mean terminal half‐life increased from 86 h at 0.5 mg/kg to 437 h at 20 mg/kg after a single dose and 16–22 days after multiple dosing. Antidrug antibodies were detected in some participants at low titers and had no effect on PK or safety. In psoriasis patients included in Part B, baseline disease severity was low (mean Psoriasis Area and Severity Index of 5.5–6.0). No meaningful differences in psoriasis measures were observed between CAL101 and placebo. In psoriasis lesions, CAL101 reduced tenascin C deposition and decreased pSTAT3, consistent with modulation of S100A4‐dependent pathways. Conclusions CAL101 demonstrated an acceptable safety profile, predictable PK and PD effects consistent with extracellular S100A4 neutralization. These findings support further clinical development of CAL101 in fibro‐inflammatory diseases.